2019
DOI: 10.1111/mmi.14356
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional initiation of a small RNA, not R‐loop stability, dictates the frequency of pilin antigenic variation in Neisseria gonorrhoeae

Abstract: Summary Neisseria gonorrhoeae, the sole causative agent of gonorrhea, constitutively undergoes diversification of the Type IV pilus. Gene conversion occurs between one of the several donor silent copies located in distinct loci and the recipient pilE gene, encoding the major pilin subunit of the pilus. A guanine quadruplex (G4) DNA structure and a cis‐acting sRNA (G4‐sRNA) are located upstream of the pilE gene and both are required for pilin antigenic variation (Av). We show that the reduced sRNA transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 99 publications
(163 reference statements)
0
13
0
Order By: Relevance
“…Mutation of the −35 sequence of the G4 sRNA promoter ( garP − 35 ) in the same FA1090 background showed reduced levels of pilin Av of 6.13 and 5.73%, which is consistent with the reduced levels of gar RNA produced when the −35 sequences was mutated. (Table 2) (33). This reduction in pilin Av frequency is significantly reduced compared to FA1090 by chi-square analysis (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutation of the −35 sequence of the G4 sRNA promoter ( garP − 35 ) in the same FA1090 background showed reduced levels of pilin Av of 6.13 and 5.73%, which is consistent with the reduced levels of gar RNA produced when the −35 sequences was mutated. (Table 2) (33). This reduction in pilin Av frequency is significantly reduced compared to FA1090 by chi-square analysis (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…gonorrhoeae strains were maintained on gonococcal medium base (Difco) modified with Kellogg supplements as described previously (64). FA1090 G4 mutant, gar −10 and gar −13 were constructed as described in reference 33.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells that successfully recombined the multisite G4 mutations were identified by screening the piliated clones in pools by PCR. Briefly, clones were individually stored in glycerol at −80°C, and pools of 10 clones were tested by using a primer, multimutG4_2, that anneals only to G4 sites that carry the desired mutations, paired with RTG4-3R ( 42 ), which binds in the beginning of the pilE locus. Positive pools were recreated by PCR using individual clones as the templates; then the promoter was amplified and sequenced with USS2 ( 43 ) and pilAREV, and the pilE locus was amplified and sequenced with PilRBS and SP3A ( 39 ).…”
Section: Methodsmentioning
confidence: 99%
“…A cis-acting small RNA called gar was detected in the upstream region of the major pilin locus pilE which harbours 12 GC base pairs with the potential to form a guanine quadruplex (G4) structure. It could be shown that transcription of gar opens the DNA duplex, thereby allowing the now single-stranded G-rich strand to form the G4 structure which is required for the homologous recombination reaction by which silent pilS copies are inserted into the pilE expression locus [20,21]. The sRNA NrrF was first observed in a screen for transcripts controlled by the ferric uptake regulator protein Fur in the closely related pathogen N. meningitidis [22] and later its expression was also reported in Ng [23].…”
Section: Introductionmentioning
confidence: 99%